In Vitro Organogenesis of Two Sansevieria trifasciata Cultivars on Different Concentrations of Benzyladenine (BA) - Yusnita Yusnita; Wiry Pungkastiani; Dwi Hapsoro (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
In vitro regeneration of buds and shoots via organogenesis in two genotypes of snake plants (Sansevieria trifasciata) were established. Leaf segments (1 x 1cm) of 'Hahnii' and 'Lorentii' were cultured on Murashige and Skoog (MS) basal medium containing 2,4- dichlorophenoxyacetic acid (2,4-D) for 1 week, transferred into MS medium without plant growth regulator (MS0) for 1 week, and then cultured on MS medium containing different concentrations of N6-benzyladenine (BA) at 0, 0.1, 0.25, 0.5, 1.0 and 2.0 mg/l in three times of serial passages with 4 week intervals. The results showed that regeneration of S. trifasciata was established via indirect organogenesis. 'Lorentii' was more responsive on shoot regeneration than 'Hahni'. The most suitable BA concentration for shoot bud and shoot regeneration for both cultivars was 2 mg/l. Explants of 'Lorentii' cultured on MS medium containing 2.0 mg/l BA produced 8.6 shoot buds and 3.4 shoots per explant after 14 weeks. Shoots derived from both cultivars were successfully ex vitro rooted and acclimatized in the greenhouse with high survival rate, i.e., from 96 -100%. Keywords : organogenesis, Sansevieria trifasciata 'Hahnii' and 'Lorenti', benzyladenine